2019
DOI: 10.29328/journal.jnnd.1001024
|View full text |Cite
|
Sign up to set email alerts
|

Carbonic Anhydrase I modifies SOD1-induced motor neuron toxicity in Drosophila via ER stress pathway

Abstract: Background: Drosophila models of amyotrophic lateral sclerosis (ALS) have been widely used in understanding molecular mechanisms of ALS pathogenesis as well as discovering potential targets for therapeutic drugs. Mutations in the copper/zinc superoxide dismutase (SOD1) cause ALS by gain of toxic functions and induce toxicity in fl y motor neurons. Results: In this study, we have determined that human carbonic anhydrase I (CA1) can alleviate mutant SOD1-induced motor neuron toxicity in the transgenic fl y model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Our genetic analyses found a strong pQTL for carbonic anhydrase IV, which is a target for Acetazolamide. Several studies have reported that the expression of Carbonic Anhydrase IV is altered in the motor neurons of Amyotrophic lateral sclerosis patients 42,43 . Acetazolamide is a carbonic anhydrase inhibitor 44 , used to treat glaucoma, epilepsy and altitude sickness 45 .…”
Section: Mendelian Randomization To Identify Novel Biomarkers and Drumentioning
confidence: 99%
“…Our genetic analyses found a strong pQTL for carbonic anhydrase IV, which is a target for Acetazolamide. Several studies have reported that the expression of Carbonic Anhydrase IV is altered in the motor neurons of Amyotrophic lateral sclerosis patients 42,43 . Acetazolamide is a carbonic anhydrase inhibitor 44 , used to treat glaucoma, epilepsy and altitude sickness 45 .…”
Section: Mendelian Randomization To Identify Novel Biomarkers and Drumentioning
confidence: 99%
“…Our genetic analyses found a strong pQTL for carbonic anhydrase IV, which is a target for Acetazolamide. Several studies have reported that the expression of Carbonic Anhydrase IV is altered in the motor neurons of Amyotrophic lateral sclerosis patients 48,49 . Acetazolamide is a carbonic anhydrase inhibitor 50 , used to treat glaucoma, epilepsy and altitude sickness 51 .…”
Section: Mendelian Randomization To Identify Novel Biomarkers and Drumentioning
confidence: 99%